Integrated Use of Geoelectrical Resistivity and Geochemical Analysis to Assess the Environmental Impact on Soil and Groundwater at Erbil Dumpsite, West of Erbil City - Iraqi Kurdistan Region - Gardi, Sirwa Q. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Water is one of the most important commodities which people and other creatures have exploited more than any other resources for their survival. Many parts of Erbil City and surroundings rely on groundwater reserves for drinking and other purposes. The study area lies within Erbil plain, some 10 km west of Erbil City. The study is based on the electrical resistivity method as a tool for assessing the environmental impact on soil and groundwater. Soil and water samples were collected close to Erbil dumpsite to assess the baseline data. 28 vertical electrical sounding points were taken by Schlumberger array along three geoelectrical sections. These sections revealed five zones of alternating clastic sediments with lateral changes which represent the Bai Hassan Formation. The average depth from the surface to the top of the aquifer is about 80 m. The geoelectrical sections revealed that the septic tank discharge valleys have been polluting the soil in two zones in the vicinity of the household septic discharge site. On the other hand, no adverse impact on groundwater quality is anticipated in the present project. The geophysical method utilized in this study is fast, efficient, and cost-effective in delineating the extent of the probable contamination zone(s).